National Education Policy (NEP)-2020: Local Languages - Vanitha P. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2023)
Modern education is becoming a national concern with a new set of goals and objectives. This policy aims to transform Indian society into a sustainable, equitable, and vibrant knowledge society by providing high-quality education to all. The vitality of any society depends on the language spoken; if not used, both society and language face extinction. This study examines the relevance of local and indigenous languages within the National Education Policy (NEP) 2020 framework. It highlights how emphasizing the mother tongue and regional languages in primary education fosters all-round growth and secures our cultural heritage.